Kemampuan pemahaman konsep berdasarkan self-efficacy matematis dan gender dalam situasi problem-based learning - Farah Heniati Santosa; Samsul Bahri; Habibi Ratu Perwira Negara; Ahmad Ahmad (Mahesa Research Center, 2022)
The ability to understand concepts is an ability that supports students' ability to solve problems. However, psychological factors in the form of mathematical self-efficacy and gender, which are factors influencing this ability, have not been investigated much. The purpose of this study was to determine the ability to understand concepts based on mathematical self-efficacy and gender in problem-based learning situations. The one-shot case study design was applied to 70 grade 8 junior high school students in one of the schools in Mataram City selected by the purposive sampling technique. Data collection uses a concept understanding ability test, a mathematical self-efficacy questionnaire, and gender categorization. Data analysis techniques used were the one-sample t-test and the Anacova test. The results of the study show that the PBL model can assist students in developing conceptual understanding skills. Subsequent findings state that mathematical self-efficacy and gender are factors that determine students' ability to understand concepts.